Ministry of Justice Synthetic Data First Prison Iteration 2, England and Wales, 2011-2023 (UK Data Service, 2025)
The Ministry of Justice (MoJ) Data First Synthetic Data Project aims to improve engagement with Data First datasets by making synthetic versions of content available to enable more rapid development of research proposals and to thereby enhance the potential for linked administrative data to improve understanding and outcomes across justice systems. The project has led the development of two components: a dataset generation platform and an initial release of lo-fidelity, synthetic data tables. This study includes a synthetically-generated version of the Ministry of Justice Data First Prisons dataset. Synthetic versions of all 43 tables in the MoJ Data First data ecosystem have been created. These versions can be used / joined in the same way as the real datasets. As well as underpinning training, synthetic datasets should enable researchers to explore research questions and to design research proposals prior to submitting these for approval. The code created during this exploration and design process should then enable initial results to be obtained as soon as data access is granted. The Ministry of Justice Data First prisoner custodial journey dataset provides data on people held in custody in prisons and Young Offender Institutions (YOIs) in England and Wales and has been extracted from the management information system Prison National Offender Management Information System (P-NOMIS), used by His Majesty's Prisons and Probation Service (HMPPS) within prisons. Data on offenders serving custodial sentences since 2011 is expected to be complete, but sentences begun before this are included. Young Offenders are included if resident at prisons or YOIs that use P-NOMIS, however, this excludes the majority of Secure Schools and Secure Training Centres. Information is included on offender characteristics, their main offence, sentence and release: for example, age, gender, ethnicity, offence category, and key dates, providing information on movements through the system and their release and recall (if applicable). There is a separate table on safety in custody incidents involving assaults and self-harm and a table on external movements (between prisons, and into and out of prison). This includes information on the date, type and reason for the movement and the locations involved (for example specific prisons). Each record in the dataset gives information about a single person and custodial journey. As part of Data First, records have been deidentified and deduplicated, using our probabilistic record linkage package, Splink, so that a unique identifier is assigned to all records believed to relate to the same person, allowing for longitudinal analysis and investigation of repeat appearances. This aims to improve on links already made within the prison system. This opens up the potential to better understand the prison population and address questions on, for example, patterns associated with short repeated custodial sentences and what works to reduce reoffending. The Ministry of Justice Data First linking dataset can be used in combination with this and other Data First datasets to join up administrative records about people from across justice services to increase understanding around users' interactions, pathways and outcomes.